Takotsubo Syndrome and Complete Heart Block: A Diagnostic and Management Conundrum - Erik Olson MD; Zachary Manna DO; Kameron Tavokolian MD; Dhaval Desai MD; Mahim Kapoor MD (SAGE Publishing, 2023)
There is increasing evidence that Takotsubo cardiomyopathy behaves more like a highly variable and dangerous syndrome than an isolated cardiomyopathy. In this case report, we describe a case of Takotsubo cardiomyopathy complicated by complete heart block. We discuss the potential mechanisms for its etiology and examine the need for pacemaker placement.